AKTIVITAS ANTIOKSIDAN Caulerpa lentillifera J.Agardh DENGAN METODE PEREDAMAN RADIKAL BEBAS 1,1-diphenyl-2 picrylhydrazil - Handayani, Selpida; Najib, Ahmad; Wisdawati, Wisdawati; Khoiriyah, Anisatul (Jurnal Kesehatan, 2020)
Green caviar (Caulerpa lentillifera J. Agardh) contains substances which potentially act as antioxidant. This research aim to determine the antioxidant activity of Green caviar extract using free radical scavenging method by 1,1-Diphenyl-2 Picrylhydrazil (Dpph). Green caviar was extracted with sequences extraction using n-hexane, ethyl acetate, and etanol 96% with the yield value for n-hexane, ethyl acetate, and ethanol are 2.256%, 4.176%, 5.548% respectively. Furthermore, the chemical contents of each extract were identified using phytochemical screening and TLC qualitative test with n-hexane : ethyl acetate ( 8 : 2 ) as mobile phase and silica gel 60 F254 as stationary phase. The results showed that each green caviar extract has antioxidant activity with IC50 value of n- hexane extract 61.057 μg/mL identified as moderate antioxidant (50-100 μg/mL) ethyl acetate extract 41.756 μg/mL included as strong antioxidant (10-50 μg/mL), and ethanol 96 % which is 52.116 μg/mL classified as moderate antioxidant (50-100 μg/mL). Ethyl acetate is the best solvent to be used to extracting the antioxidant compounds of Green caviar.